A Maximal Description for the Real Interpolation Method in the Quasi-Banach Case. - Bergh, Jöran; Cobos, Fernando (MATHEMATICA SCANDINAVICA, 2000)
We give a maximal description in the sense of Aronszajn-Gagliardo for the real method in the category of quasi-Banach spaces.